Association between grip strength and non-alcoholic fatty liver disease: A systematic review and meta-analysis - Han, Liu; Fu, Shifeng; Li, Jianglei; Liu, Deliang; Tan, Yuyong (Frontiers in Medicine, 2022)
Background: The association between grip strength and non-alcoholic fatty liver disease (NAFLD) has been reported by recent epidemiological studies, however the results of these studies are inconsistent. This meta-analysis was conducted to collect all available data and estimate the risk of NAFLD among people with low grip strength and the risk of low grip strength among patients with NAFLD. Methods: We systematically searched several literature databases including PubMed，Web of Science, Cochrane Library and Embase from inception to March 2022. These observational studies reported the risk of NAFLD among people with low grip strength and the risk of low grip strength among patients with NAFLD. Qualitative and quantitative information was extracted, statistical heterogeneity was assessed using the I2 test, and potential for publication bias was assessed qualitatively by a visual estimate of a funnel plot. Results: Of the citations, 10 eligible studies involving 76676 participants met inclusion criteria. The meta-analysis of 7 cross-section studies (69757 participants) showed that people with low grip strength had odds of NAFLD that were 3.32 times as high as normal grip strength (summary OR=3.32, 95%CI: 1.91-5.75). In addition, the meta-analysis of 4 studies (14920 participants) reported that patients with NAFLD had odds of low grip strength that were 3.31 times as high as normal people (summary OR=3.31, 95%CI:2.45-4.47). Conclusion: In this meta-analysis, a significantly increased risk of NAFLD among people with low grip strength, and a higher risk of low grip strength among patients with NAFLD.